Synthesis and characterization of analogues of glycine-betaine ionic liquids and their use in the formation of aqueous biphasic systems - Pereira, Matheus M. (2021)
A series of novel analogues of glycine-betaine ionic liquids (AGB-ILs), viz. 1-(4-ethoxy-4-oxobutyl)-1-methylpyrrolidin-1-ium, N,N,N-tri(n-butyl)(4-ethoxy-4-oxobutyl)-1-phosphonium and N,N,N-trialkyl(4-ethoxy-4-oxobutyl)-1-aminium cations with ethyl, n-propyl and n-butyl alkyl chains, combined with the bromide anion, have been synthesized and characterized. Their synthesis and characterization by spectroscopic methods and elemental analysis is here reported. These ILs were further characterized in what concerns their thermal properties and ecotoxicity against Allvibrio fischeri, and compared with the commercial tetra(n-butyl)ammonium and tetra(n-butyl)phosphonium bromide. The novel AGB-ILs described in this work have low melting points, below 100 °C, display high degradation temperatures (180–310 °C), and low toxicity as shown by being harmless or practically harmless towards the marine bacteria Allvibrio fischeri. Finally, the ability of the synthesized AGB-ILs to form aqueous biphasic systems with potassium citrate/citric acid (at pH 7) was evaluated, and the respective ternary phase diagrams were determined. It is shown that the increase of the cation alkyl chain length facilitates the creation of ABS, and that phosphonium-based ILs present a slightly better separation performance in presence of aqueous solutions of the citrate-based salt.